The aetiology of diarrhoea, pneumonia and respiratory colonization of HIV-exposed infants randomized to breast- or formula-feeding. (2nd July 2016) - Zash, Rebecca M.; Shapiro, Roger L.; Leidner, Jean; Wester, Carolyn; McAdam, Alexander J.; Hodinka, Richard L.; Thior, Ibou; Moffat, Claire; Makhema, Joseph; McIntosh, Kenneth; Essex, Max; Lockman, Shahin
Abstract : Background: Diarrhoea and pneumonia are common causes of childhood death in sub-Saharan Africa but there are few studies describing specific pathogens. Objectives: The study aimed to describe the pathogens associated with diarrhoea, pneumonia and oropharyngeal colonization in children born to HIV-infected women (HIV-exposed infants). Methods: The Mashi Study randomized 1200 HIV-infected women and their infants to breastfeed for 6 months with ZDV prophylaxis or formula-feed with 4 weeks of ZDV. Children were tested for HIV by PCR at 1, 4, 7, 9 and 12 months and by ELISA at 18 months. Pre-defined subsets of children were sampled during episodes of diarrhoea ( n = 300) and pneumonia ( n = 85). Stool was tested for bacterial pathogens, rotavirus and parasites. Children with pneumonia underwent bacterial blood culture, and testing of nasopharyngeal aspirates for viral pathogens by PCR. Oropharyngeal swabs were collected from a consecutive subset of 561 infants at the routine 3-month visit for bacterial culture. Results: The median age (range) at sampling was 181 days for diarrhoea (0–730) and 140 days for pneumonia (2–551). Pathogens were identified in 55 (18%) children with diarrhoea and 32 (38%) with pneumonia. No differences in pathogens by child HIV status (HIV-infected vs HIV-uninfected) or feeding strategy were identified. Campylobacter was the most common diarrhoeal pathogen (7%). Adenovirus (22%) and other viruses (19%) were the primary pathogens isolated during pneumonias. More formula-fed infants had oropharyngeal colonization by pathogenic Gram-negative bacteria (16.8% vs 6.2%, P = 0.003), which was associated with a non-significant increased risk of pneumonia (OR 2.2, 95% CI 0.8–5.7). Conclusion: A trend toward oropharyngeal bacterial colonization was observed in formula-fed infants. Although viruses were most commonly detected during pneumonia, respiratory colonization by Gram-negative bacteria may have contributed to pneumonia in formula-fed infants.